Industrial Gas Turbine Engine Off-Design Performance Improvement Controlling Cooling Air Flow - Moroz, Leonid; Burlaka, Maksym; Barannik, Valentyn (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2018)
The modern gas turbine engine has been used in current power generation industry for almost half a century. They are designed to operate with the best efficiency during normal operating conditions and at specific operating points. However, due to power grid demands, different ambient temperatures, fuel types, relative humidity and driven equipment speed the gas turbine units have to work today on partial load too, which can affect the hot gas path condition and life expectancy. At these off-design conditions, gas turbine’s efficiency and life deterioration rate might significantly deviate from the design specifications. In this paper, a digital twin concept for gas turbine unit off-design performance prediction (AxSTREAM® platform) is used. The description of created digital twin is presented. The validation of proposed gas turbine unit digital twin is carried out by comparison with literature source test data. The GTU performance estimation controlling cooling air at part load modes using digital twin was performed.